Integrated analysis of source-specific risks for PM2.5-bound metals in urban, suburban, rural, and industrial areas. (15th April 2021) - Hsu, Chin-Yu; Chi, Kai-Hsien; Wu, Chih-Da; Lin, Sheng-Lun; Hsu, Wen-Chang; Tseng, Chun-Chieh; Chen, Mu-Jean; Chen, Yu-Cheng
Abstract: The levels and characteristics of atmospheric metals vary in time and location, can result in various health impacts, which increases the challenge of air quality management. We aimed to investigate PM2.5 -bound metals in multiple locations and propose a methodology for comparing metal elements across study regions and prioritizing source contributions through integrated health risk assessments. PM2.5 -bound metals were collected in the urban, suburban, rural, and industrial regions of Taiwan between 2016 and 2018. We incorporated the positive matrix factorization (PMF) with health risk assessments (considering estimates of the margin of exposure (MOE) and excess cancer risk (ECR)) to prioritize sources for control. We found that the concentrations of Fe, Zn, V, Cu, and Mn (industry-related metals) were higher at the industrial site (Kaohsiung) and Ba, Cr, Ni, Mo, and Co (traffic-related metals) were higher at the urban site (Taipei). The rural site (Hualian) had good air quality, with low PM2.5 and metal concentrations. Most metal concentrations were higher during the cold season for all study sites, except for the rural. Ambient concentrations of Mn, Cr, and Pb obtained from all study sites presents a higher health risk of concern. In Kaohsiung, south Taiwan, PM2.5 -bound metals from the iron ore and steel factory is suggested as the first target for control based on the calculated health risks (MOE < 1 and ECR > 10 −6 ). Overall, we proposed an integrated strategy for initiating the source management prioritization of PM2.5 -bound metals, which can aid an effort for policymaking. Graphical abstract: Image 1 Highlights: As, Sb, and Pb levels obtained from the suburban site were significantly high. Ambient Mn, Cr, and Pb concentrations are of concern in all four study areas. PM2.5 -bound metals from the iron ore and steel factory are first prioritized to be controlled.